War in 140 characters: how social media is reshaping conflict in the twenty-first century - Patrikarakos, David (Basic Books, 2017)
"War in 140 Characters examines the role of social media and other forms of 'new media' in changing the face of modern warfare. War is, more than ever, a clash of narratives--with each state/party fighting to control the spread of information and project their narrative to the outside world. Social media has shattered traditional hierarchies between the state and its citizens, enabling the individual or networks of individuals to influence the direction of conflict to a degree previously thought impossible. State militaries now employ official Social Media warriors to influence the narrative online; in Russia, paid trolls flood the internet with pro-Russian tweets, blog posts, and comments in order to create the sense of "authentic" support for the annexation of Crimea. Even private civilians can single-handedly alter the course of war. New media has expanded the arena of conflict into the virtual world, which is every bit as real and often more important than the fighting on the ground. Whether you are a president or a terrorist, if you don't understand how to deploy the power of media effectively you may win the odd battle but you will lose a twenty-first century war. War in 140 Characters provides a new narrative for modern warfare, exploring the way social media has transformed the way that we fight, win, and consume wars, and what that means for the world going forward."--Provided by publisher